2013
DOI: 10.5624/isd.2013.43.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The chronology of second molar development in Brazilians and its application to forensic age estimation

Abstract: PurposeThis study investigated the possible correlation between the mineralization of the second molars and the chronological age of a sample population of the state of Paraiba, Brazil.Materials and MethodsOne thousand eight hundred fifty-four digitized panoramic images using a scanner of a private dental radiology service were obtained in six months. Of these, 457 were selected from patients aged 4.6 to 16 years who met certain criteria. The images were assessed twice by a radiologist with 5 years experience.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
8
0
3
Order By: Relevance
“…The characteristics of each stages according to Demirjian index (DI) (Fig. 1) were as follows (23): (A) Calcification of the occlusal points without fusion can be observed; (B) Fusion of the calcified points forms the occlusal surface; (C) Enamel formation at the occlusal surface is complete, dentin formation is observed, the pulp chamber has a curved shape, and no pulp horns are visible; (D) Crown formation is complete to the level of cemento-enamel junction, root formation is observed, the pulp horns are visible, and the walls of the pulp chamber are curved to the cervical region; (E) The walls of the pulp chamber are straight, the root length is less than the crown height, and radicular bifurcation is observed in the molar; (F) The walls of the pulp chamber form an isosceles triangle and the apex ends in a funnel shape, the root length is equal to or longer than the crown height, bifurcation has developed to give the roots a more definite form; (G) The walls of the root canal are parallel and its apical end is partially open; and (H) The apical end of the root canal is complete and the periodontal membrane is distinct. A dental radiologist (JWC) interpreted the panoramic radiographs of the mandibular second premolar and molar as one of 8 stages (A to H).…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of each stages according to Demirjian index (DI) (Fig. 1) were as follows (23): (A) Calcification of the occlusal points without fusion can be observed; (B) Fusion of the calcified points forms the occlusal surface; (C) Enamel formation at the occlusal surface is complete, dentin formation is observed, the pulp chamber has a curved shape, and no pulp horns are visible; (D) Crown formation is complete to the level of cemento-enamel junction, root formation is observed, the pulp horns are visible, and the walls of the pulp chamber are curved to the cervical region; (E) The walls of the pulp chamber are straight, the root length is less than the crown height, and radicular bifurcation is observed in the molar; (F) The walls of the pulp chamber form an isosceles triangle and the apex ends in a funnel shape, the root length is equal to or longer than the crown height, bifurcation has developed to give the roots a more definite form; (G) The walls of the root canal are parallel and its apical end is partially open; and (H) The apical end of the root canal is complete and the periodontal membrane is distinct. A dental radiologist (JWC) interpreted the panoramic radiographs of the mandibular second premolar and molar as one of 8 stages (A to H).…”
Section: Methodsmentioning
confidence: 99%
“…In these studies, tables for dental age estimation were formed according to mineralization stages and eruption positions in various age groups. These techniques were specific to the populations in which they were developed and might be misleading for other populations 4,5. In two of the early studies, it was reported that the Demirjian technique, which was developed on the basis of French-Canadian children, considerably overestimated the dental age for Turkish children 6,7.…”
Section: Introductionmentioning
confidence: 99%
“…Şu ana kadar dişlerin gelişim ve sürme aşamaları üzerine yapılan pek çok çalışmada popülasyonlar arasında kayda değer ölçüde varyasyon olduğu vurgulanmıştır (2,3,5,9,(12)(13)(14)(15)(20)(21)(22)(23)(24)(25)(26). Dolayısıyla bu tür atlasların hangi toplum için oluşturulmuş ise o topluma spesifik olduğu ve en iyi sonuçları vereceği akıldan çıkarılmamalıdır.…”
Section: Discussionunclassified
“…Bugüne kadar bu iki kritere dayandırılan ve değişik doğruluk oranlarında yaş tahminine imkân veren pek çok teknik geliştirilmiştir (1). Bu tekniklerin çoğu popülasyonlara özgüdür ve diğer popülasyonlarda kullanımı hatalı tahminlere yol açabilir (2,3). Güvenilirliği kanıtlanmış tekniklerin farklı etnik popülasyonlarda kullanımı için validasyon çalışmalarının yapılması gereklidir (4).…”
Section: Gi̇ri̇ş Ve Amaçunclassified